PERM1—An Emerging Transcriptional Regulator of Mitochondrial Biogenesis: A Systematic Review - Soares Menezes, Eveline; Wu, Zeyu; Renwick, John R. M.; Moran-MacDonald, Andres; Gurd, Brendon J. (Genes, 2024)
Background/Objectives: This systematic review aims to explore the role of PERM1 across different organisms, tissues, and cellular functions, with a particular focus on its involvement in regulating skeletal muscle mitochondrial biogenesis. Methods: This systematic review follows The PRISMA 2020 Statement. We used the Covidence systematic review software for abstract/title screening, full-text review, and data extraction. The review included studies that examined PERM1 expression or activity in skeletal muscle, heart, and adipose tissue and/or cells, from mice, rats, and humans, and involved exercise or disease models. Risk of bias was assessed using the Cochrane Collaboration tool, and the data were extracted and synthesized qualitatively, with bioinformatic analyses performed using the MetaMEx database. Results: Twenty-one studies were included in our data extraction process, where 10 studies involved humans, 21 involved mice, four involved rats, and 11 involved cells. Conclusions: PERM1 in skeletal muscle increases with endurance exercise, affecting muscle function and oxidative metabolism, but its role in humans is not well understood. In cardiac tissue, PERM1 is vital for function and mitochondrial biogenesis purposes, but decreases with disease and pressure overload. Our review synthesizes the current understanding of PERM1’s function, raises awareness of its role in mitochondrial regulation, and identifies key areas for future research in the field.